Multiobjective Optimization of Hard Turning on OHNS Steel Using Desirability and TOPSIS Approaches - C. Manikandan; B. Rajeswari; Dhanesh G. Mohan; R. M. Aravind (Advances in Materials Science and Engineering)
Machining hard materials with 45–48 HRC is difficult in turning operation because of the improvident cutting parameter selections for the operation. The OHNS (AISI/SAE-01–48HRC) steel is mainly preferred for the production of shafts, gears, cams, and press tools. The OHNS material was turned at a dry state using VP-coated carbide inserts. The seventeen experimental trials were designed by central composite design (CCD) with different levels of cutting parameters, like feed rate, cutting speed, and depth of cut. Design Expert-11 software desirability approach and TOPSIS (Technique for Order Preference by Simulating the Ideal Solution) were used to analyse the experimental results to obtain a single optimal solution that defines better results on metal removal rate (MRR) and surface finish (Ra). RSM solution with 81.3% desirability, the cutting speed of 60 m/min, feed rate of 0.08 mm/rev, and depth of cut 1 mm as the optimal cutting parameters; similarly, TOPSIS algorithm calculation identifies the cutting parameter combinations, such as 40 m/min cutting speed, 0.09 mm/rev feed rate, and 1 mm depth cut to enrich the quality of the machined steel; however, the desirability approach cutting parameter setting is better for the surface finish achievement, while TOPSIS solution is better to obtain significant MRR. The confirmation test results validated for the predicted values of both approaches; as such, the experimental results were maintained better convenience than the predicted one. For the optimum cutting parameter combinations, an MRR of 22.032 gm/min and surface roughness of 0.781 μm were obtained at 60 m/min cutting speed, 0.08 mm/rev feed rate, and 1 mm depth of cut.